The Quest for Global Dominance Transforming Global Presence into Global Competitive Advantage - Gupta, Anil K. (John Wiley & Sons, Incorporated, 2015)
Anil K. Gupta, Vijay Govindarajan, and Haiyan Wang are among the most distinguished experts in the field of globalization. In The Quest for Global Dominance they present the lessons from their twenty-year study of over two hundred corporations. They argue that, in order for a company to create and maintain its position as a globally dominant player, executives must ensure that their company leads its industry in the following four essential tasks: Identifying market opportunities worldwide and pursuing them by establishing the necessary presence in all key markets Converting global presence into global competitive advantage by identifying and developing the opportunities for value creation that global presence offers Cultivating a global mindset by viewing cultural and geographic diversity as an opportunity, not just a challenge Leveraging the rise of emerging markets especially China and India to transform the company's growth prospects, global cost structure, and pace of innovation